Bifunctional scaffolds for the photothermal therapy of breast tumor cells and adipose tissue regeneration. Issue 46 (8th November 2018) - Wang, Xiuhui; Zhang, Jing; Li, Jingchao; Chen, Ying; Chen, Yazhou; Kawazoe, Naoki; Chen, Guoping
Abstract : Bifunctional composite scaffolds of gold nanorods and gelatin can ablate tumor cells and promote the adipogenic differentiation of stem cells. Abstract : Breast cancer is a major public health issue, whose morbidity and mortality are increasing across the world. It is still a challenge to completely ablate breast tumor cells and reconstruct tumor-initiated breast defects after surgical resection. Porous scaffolds with hyperthermal and tissue regeneration functions are a desirable option to achieve these effects. In this study, bifunctional composite porous scaffolds of gold nanorods (AuNRs) and gelatin with well controlled pore structures were prepared by introducing AuNRs into the porous matrices of gelatin and using ice particulates as a porogen material. The AuNRs–gelatin composite scaffolds exhibited a high photothermal conversion effect, whose photothermal temperature could be modulated by the amount of incorporated AuNRs, NIR laser power intensity and irradiation time. The AuNRs–gelatin composite scaffolds exhibited an excellent photothermal ablation capacity toward breast tumor cells in vitro and in vivo . Furthermore, the AuNRs–gelatin porous scaffolds supported cell adhesion and promoted the proliferation and adipogenic differentiation of human bone-marrow derived mesenchymal stem cells (hMSCs). Consequently, the AuNRs–gelatin scaffolds could not only provide photothermal therapy for breast tumors but also promote the adipogenic differentiation of stem cells for adipose tissue regeneration.